Extending Peri-Personal Space in Immersive Virtual Reality: A Systematic Review - Cagatay Karakoc; Chiara Lucifora; Simona Massimino; Sebastiano Nucera; Carmelo Mario Vicario (Virtual Worlds)
Peri-personal space (PPS) refers to the area immediately surrounding our body where interactions with objects and others occur. Immersive virtual reality (IVR) offers a controlled and adaptable environment, enabling the precise modulation of PPS boundaries. This provides significant benefits across various fields, including enhancing spatial awareness, advancing therapeutic interventions, and improving ergonomic designs. This systematic review aims to synthesize and evaluate the existing literature on this topic through various methodologies. To achieve this, three databases, PubMed, Scopus, and Web of Science, were searched following the PRISMA framework. Twenty studies met the eligibility criteria, were assessed for quality, and were included in the review. Across all studies, IVR was utilized to provide multisensory interactions and implement methods were used to manipulate PPS boundaries. The review categorizes PPS extension methods into three main domains: tool-use extension, extension related to tool use, social interaction extension, and embodiment-related extension. The findings confirm IVR’s potential to expand PPS boundaries and offer recommendations for leveraging this technology in future research. This work highlights the importance of IVR in advancing our understanding of PPS and its practical applications across diverse contexts.